2014
DOI: 10.1007/s10120-014-0395-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of plasma treatment on gastric cancer cells

Abstract: Background Treatment of peritoneal carcinomatosis arising from gastric cancer remains a considerable challenge. In recent years, the anticancer effect of nonequilibrium atmospheric pressure plasma (NEAPP) has been reported in several cancer cell lines. Use of NEAPP may develop into a new class of anticancer therapy that augments surgery, chemotherapy, and radiotherapy. Method Gastric cancer cells were assessed for changes in cell morphology and rate of proliferation after treatment with NEAPP-exposed medium (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 37 publications
4
36
0
Order By: Relevance
“…Cold plasma affects biological targets not only directly but also indirectly through the medium, which has broadened the potential applications of non-thermal atmospheric pressure plasma in medicine41424344454647484950. We have demonstrated that plasma-irradiated medium, also called plasma-activated medium (PAM), has anti-tumor effects against glioblastoma5152, as well as ovarian5354, gastric55, pancreatic56, and lung cancer cells57. Plasma interacts with oxygen, nitrogen, and water in air to produce various radicals, such as hydroxyl radicals and nitric oxide.…”
mentioning
confidence: 99%
“…Cold plasma affects biological targets not only directly but also indirectly through the medium, which has broadened the potential applications of non-thermal atmospheric pressure plasma in medicine41424344454647484950. We have demonstrated that plasma-irradiated medium, also called plasma-activated medium (PAM), has anti-tumor effects against glioblastoma5152, as well as ovarian5354, gastric55, pancreatic56, and lung cancer cells57. Plasma interacts with oxygen, nitrogen, and water in air to produce various radicals, such as hydroxyl radicals and nitric oxide.…”
mentioning
confidence: 99%
“…This type of selective targeting of cancer cells is ideally suited to cancer therapy. An antitumor effect of PAM treatment has been reported for a broad range of cancer and cancer cell types . Details regarding the intracellular molecular mechanism of cell death in cancers treated with PAM and the interaction of PAM with cells were reported by Tanaka et al PAM treatment was found to downregulate the kinase activity of both AKT and ERK in the PI3K/AKT signaling pathway, as well as the Ras/MAPK signaling pathway, in glioblastoma brain tumor cells .…”
Section: Introductionmentioning
confidence: 95%
“…Another 2015 study considered the impact of PAM on the cell morphology and proliferation rate of gastric cancer cells. 101 The impact on cancer cells was dependent upon plasma exposure time during PAM preparation, the cell line, and the initial cell concentration. Some cell lines were more resistant to PAM treatment, but this could be overcome by increasing the plasma treatment time during preparation.…”
Section: App Applicationsmentioning
confidence: 99%